A Longitudinal Overview Of The Situation Of Families From An Inclusion Perspective Environmental And Family Factors Associated With Special Educational Needs - Vida, Gergő; Faragó, Beatrix (Journal of Ecohumanism, 2024)
While diagnostic systems such as the ICD-11 and DSM-5 exclude social and economic factors as potential causes of disability and learning problems, statistics from the educational and social systems of many European countries contradict this approach. Our research focuses on the compensatory strategies of the education system in Hungary, as the literature suggests that disability, differential development, and learning problems are a major stress factor and problem to be solved for the education system, the individual, and the family.An examination of the Hungarian system is particularly warranted in light of the results of the most recent PISA surveys, which show that educational failure in this country is strongly correlated with family background. Our research has demonstrated that special educational needs are more strongly related to family background and social factors than to other factors, which may be indirect evidence that family and social background are significant variables in the management of stress. In the presence of an unfavorable social background, disability and learning disabilities place greater pressure and stress on the family, increasing the risk of disconnection and early school leaving. Consequently, the role of proper education and cooperation is of paramount importance, as it is clear that neither the family nor the education system alone can be successful in dealing with stress.Our research has shown that resilience is intimately connected to parental factors, which are strongly influenced by parental education. Therefore, stress management and the avoidance of additional stress can be linked to the education system, even if indirectly. Furthermore, the formal education system is a crucial site for fostering effective attitudes, underscoring the importance of formal education in shaping attitudes and preparing individuals for lifelong learning, rather than simply imparting knowledge. To effectively manage stress, individuals must continuously develop and learn new coping strategies, and consciously cultivate resilience, as future stressors are unpredictable.